Shaping territorial agri-food systems through social innovations: The example of Valposchiavo, Switzerland - Paul Froning; Rike Stotten (Italian Review of Agricultural Economics (REA), 2024)
Territorial agri-food systems can be characterized as social innovations that challenge corporate food governance. These systems involve a diverse array of actors operating at the local level, with the shared objective of promoting locally sourced and environmentally sustainable products. To gain deeper insights into the interplay of social innovation and territorial governance, we investigated the case of Valposchiavo, Switzerland. In this unique setting, diverse actors have initiated an innovative approach to territorial development, emphasizing the revalorizing of local resources. To unravel the intricacies of the development process, we applied the territorial social innovation framework, specifically tailored for analyzing the role of social innovations within Valposchiavo's territorial agri-food system. Our research incorporated existing interviews and supplemented them with problem-centred interviews conducted in the field. Results underscore that the development approach of 100% Valposchiavo constitutes a territorial social innovation. This innovation is evident in the formation of diverse local collaborations, establishing novel multi-actor settings within the territorial agri-food system, with an emphasis on collective values aligned with organic agriculture. Our study also identifies an innovative territorial governance approach aimed at obtaining certification as an organic region in the future. This signifies a proactive step towards creating a sustainable and certified organic framework to institutionalize territorial agri-food system.
Keywords: Q; R; 330; Agro-food networks; Agro-food systems; Organic regions; Social innovation; Territorial governance; Valposchiavo